2022
DOI: 10.1007/s13399-022-02570-6
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm shift towards production of sustainable bioenergy and advanced products from Cannabis/hemp biomass in Canada

Abstract: The global cannabis ( Cannabis sativa ) market was 17.7 billion in 2019 and is expected to reach up to 40.6 billion by 2024. Canada is the 2nd nation to legalize cannabis with a massive sale of $246.9 million in the year 2021. Waste cannabis biomass is managed using disposal strategies (i.e., incineration, aerobic/anaerobic digestion, composting, and shredding) that are not good enough for long-term environmental sustainability. On the other hand, greenhouse gas emissions and the rising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 166 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Cannabis biomass can be used as a feedstock to produce various biofuels and biochemicals 151]. Various research groups have reported production of ethanol 9.2-20.2 g/L, hydrogen 13.5 mmol/L, lipids 53.3%, biogas 12%, and biochar 34.6% from Cannabis biomass [89][90][91][92][93][94][95][96]. Biodiesel can be primarily produced from hemp seed oil 151].…”
Section: Industrial Cannabis Sativa (Hemp)mentioning
confidence: 99%
“…Cannabis biomass can be used as a feedstock to produce various biofuels and biochemicals 151]. Various research groups have reported production of ethanol 9.2-20.2 g/L, hydrogen 13.5 mmol/L, lipids 53.3%, biogas 12%, and biochar 34.6% from Cannabis biomass [89][90][91][92][93][94][95][96]. Biodiesel can be primarily produced from hemp seed oil 151].…”
Section: Industrial Cannabis Sativa (Hemp)mentioning
confidence: 99%
“…Scientific queries on the feasibility analysis of hemp seed and fibers (Aydoğan et al., 2020; Fortenbery & Bennett, 2004; Fortenbery & Mick, 2014; Hanchar, 2019; Schluttenhofer & Yuan, 2017) show regional variability in profit (Dogbe & Revoredo‐Giha, 2022; Johnson, 2013). Additionally, many studies (e.g., Brar et al., 2022; Finnan & Styles, 2013; Prade, 2011; Rehman et al., 2013) are unequivocal about the economic benefit of hemp feedstocks for bioenergy generation. Recent studies comparing the cost efficiency of manufactured hemp‐based products against the slew of bio‐based and synthetic bio‐based products has resulted in ambiguity about the relative competitiveness of individual hemp products.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis sativa L. is an annual and predominantly dioecious species originating from Asia, with a long domestication history because of its many traditional uses, including textile fibre source, seeds for nutrition, and medicinal or recreational drug use ( Andre et al., 2016 ; Ren et al., 2021 ). In modern times the interest in this multi-purpose plant has experienced a continuous expansion due to the increasing new applications in different areas, such as nutrition, food additives, and nutraceuticals ( Ascrizzi et al., 2020 ; Rupasinghe et al., 2020 ); emerging green materials ( Moscariello et al., 2021 ; Sorrentino, 2021 ); production of bioethanol and biofuels ( Brar et al., 2022 ); or bioremediation and restoration of contaminated water and soils ( Loffredo et al., 2021 ; Pudełko et al., 2021 ). However, the most economically attractive feature is the plant richness in different bioactive phytochemicals with promising pharmacological and therapeutic applications such as flavonoids, terpenes, and, particularly, phytocannabinoids ( Andre et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most economically attractive feature is the plant richness in different bioactive phytochemicals with promising pharmacological and therapeutic applications such as flavonoids, terpenes, and, particularly, phytocannabinoids ( Andre et al., 2016 ). So far, the cannabis market has experienced continuous growth, and it is expected to reach up to 40.6 billion by 2024 ( Brar et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%